(untitled) (Jurnal Ilmu Komunikasi, 2020)
Stand Up Comedy is a form of comedy performance art, which are monologuing at the performance by one man to entertain the audience. Usually form by live show (directly) and the comedians doing one man show. This study aims to expanding knowledge about Rhetorics and knowing the process of producing messages in Stand Up Comedy Materials. This study uses the theory of Aristotelelian rhetoric and Barbara O’ Keffee’s message production theory by using constructivist qualitative research methods, where data collection technique used are observation, interviews, and documentation. The results of the study found out that there is a relation between Stand Up Comedy and Rhetorical activities, public communication in particular. Those statement strengthened by the results of the study found that each comic uses the five–rhetorical canon technique which is discovery, arrangement, style, memory, and delivery to produce the message of Materials. The study of Message Design Logics (Plans and Goals), found out that the informant designing plans to get excellent impression when the message hits the audience, and the informant also designing Goals to entertain, educating, and to put audience doing better action by the materials message. The Advice given by author for Stand Up Indo Lampung community is to continue maintaining consistency to accommodating the Stand Up Comedy enthusiasts in the Lampung region.